2016
DOI: 10.1016/j.combustflame.2016.02.032
|View full text |Cite
|
Sign up to set email alerts
|

5 kHz thermometry in a swirl-stabilized gas turbine model combustor using chirped probe pulse femtosecond CARS. Part 2. Analysis of swirl flame dynamics

Abstract: We have performed a detailed analysis of the temperature field in a turbulent swirl flame operating with a self-excited thermo-acoustic instability. The temperature field was measured using 5 kHz chirpedprobe-pulse (CPP) femtosecond (fs) coherent anti-Stokes Raman scattering (CARS). The measurements are described in detail in the part 1 companion article. In this paper, part 2, a detailed analysis of the time-resolved temperature measurements and simultaneous pressure measurements is performed to provide insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…While the recent effort to study flow and flame dynamics and structures in turbulent combustion remained strong, both experimentally [32][33][34][35][36] and numerically, [37][38][39][40][41][42] very few studies joined the strengths of experimental and numerical tools to gain insight into the vortical structures that we observe in such reacting flows. The goal of this work is to combine experiments and simulations in order to identify the origin and dynamics of flame and flow structures in a model swirl burner.…”
Section: A Goal and Outline Of The Current Papermentioning
confidence: 99%
“…While the recent effort to study flow and flame dynamics and structures in turbulent combustion remained strong, both experimentally [32][33][34][35][36] and numerically, [37][38][39][40][41][42] very few studies joined the strengths of experimental and numerical tools to gain insight into the vortical structures that we observe in such reacting flows. The goal of this work is to combine experiments and simulations in order to identify the origin and dynamics of flame and flow structures in a model swirl burner.…”
Section: A Goal and Outline Of The Current Papermentioning
confidence: 99%
“…Femtosecond (fs) coherent anti‐Stokes Raman scattering (CARS) spectroscopy has emerged as a powerful tool for temperature and concentration measurements over the last decade . Previous studies have shown that Fourier transform‐limited (FTL) pump and Stokes pulses with pulse duration on the order of 50–100 fs can generate giant Raman coherences in which all the Q‐branch transitions for a molecule such as N 2 are excited with nearly the same efficiency and phase .…”
Section: Introductionmentioning
confidence: 99%